Distribution and density estimates of cetaceans along the midAtlantic Ridge during summer 2004 - Waring, Gordon T.; Nottestad , Leif; Olsen , Erik; Skov , Henrik; Vikingsson , Gisli (J. Cetacean Res. Manage., 2023)
During 4 June-2 July 2004, the Norwegian R/V G.O. Sars conducted a multi-disciplinary survey along the mid-Atlantic Ridge (MAR) from the Reykjanes Ridge to north of the Azores. This provided the first systematic survey information on MAR cetacean populations. Using naked eye or 7350 hand-held binoculars, observers searched in a 140° arc centred along the ships’ heading. Eleven cetacean species and 10 other taxonomic groups were identified along 2,321km of transect effort. The sei whale (Balaenoptera borealis) and sperm whale (Physeter macrocephalus) were the most commonly sighted species (53 and 48 sightings, respectively). There were 12 sightings of the fin whale (B. physalus). There were 26, 13 and 12 sightings, respectively of the common dolphin (Delphinus delphis), pilot whale (Globicephala sp.) and striped dolphin (Stenella coeruleoalba). Density estimates of species ranged from 0.018 to 0.238 animals km–2. The precision of the estimates (CV) was low, ranging from 40% to 61%. Species distribution varied north to south; the highest aggregations of baleen whales were sighted at the Charlie Gibbs Fracture Zone (CGFZ). Sperm whales were also observed at the CGFZ as well as north of this area. Pilot whales and Atlantic white-sided dolphins (Lagenorhynchus acutus) were sighted mainly in the cold (5-16°C) and less saline (34.6-35.8‰) water masses along the Reykjanes Ridge. Conversely, common dolphins and striped dolphins were most commonly sighted south of the CGFZ in areas with warmer (12-22°C) and more saline (34.8-36.7‰) surface water temperatures.